Familial idiopathic pulmonary fibrosis in association with bone marrow hypoplasia and hepatic nodular regenerative hyperplasia: a new "trimorphic" syndrome. Issue 5 (28th April 2009) - Talbot-Smith, A; Syn, W-K; MacQuillan, G; Neil, D; Elias, E; Ryan, P
Abstract : This is the first report of familial idiopathic pulmonary fibrosis associated with hepatic nodular regenerative hyperplasia and bone marrow hypoplasia. Four members of one family presented with this triad of organ dysfunction. The response to immunosuppressive treatment was poor and all four members succumbed to the disease processes. The current literature is reviewed and mechanisms that could have been involved in the development of this new syndrome are proposed.